Pengembangan Teknologi Penangkapan Ikan Yang Ber-tanggung Jawab Di Perairan Kabupaten Labuhanbatu Provinsi Sumatera Utara - Khasahatan Siregar, Irham Huspa (Fakultas Perikanan dan Kelautan Universitas Riau, 2018)
This study was conducted in 26 January to 26 February 2015, took place in the waters of Labuhanbatu District. This study aimed to determine the development of responsible fisheries in the waters of Labuhanbatu and can provide advice to the government on the policy of responsible/sustainable fisheries development in the conservation and sustainability of fishery resources. The results showed that in the waters of Labuhanba-tu District are identified seven fishing gear : anchovies trawl (pekboat), tangkul (pengerih), longline bumper, Senangin gill nets, half gill nets, Toli shad gill nets and Heko shrimp nets. Irresponsible (unsustainable) fishing gear based on the FAO Code of Conduct is anchovy trawl (pekboat) which has a value of 1.77. While responsible (environmentally friendly) heko shrimp gill net (3.88), half gill nets (3.55), fishing gear are longline bumper has a value of 3.55, and Senangin gill nets (3.66 ). In Toli shad gill nets have a value of 3.44 which is environmental friendly but fish caught is protected species, and tangkul has a value of 2.66 also environmental friendly but the fishing line must be set as it’s not endanger the fishermen.